Corporate Social Responsibility dan Kinerja Keuangan Perusahaan: Bukti Empiris dalam Kerangka Signaling Theory - Ayu Ambang Lestari; Baiq Dinda Puspita Ayu; Arie Cahyani (AKUNTANSI 45, 2026)
Of the 11 ASEAN countries, Indonesia ranks fourth in terms of Corporate Social Responsibility (CSR) implementation, and only a small number of companies listed on the Indonesia Stock Exchange are able to achieve a ranking in the Asia Sustainability Reporting Rating. This indicates that CSR disclosure is still relatively low. This study aims to examine the impact of CSR disclosure in the economic, social, and environmental dimensions on financial performance using a signaling theory perspective. The method used is quantitative explanatory, and the population is all state-owned enterprises listed on the IDX for the period 2022-2024. The sampling technique used purposive sampling, resulting in 42 samples. The analysis tool used is multiple linear regression with SPSS 22. The results of the analysis show that CSR disclosure in the economic dimension has a significant positive effect on financial performance. Meanwhile, CSR disclosure in the environmental and social dimensions does not significantly affect financial performance. The implication of this study is that the market tends to be more responsive to CSR information directly related to the creation of a company's economic value compared to CSR information oriented towards the environment and social.